Activation of Protic, Hydridic and Apolar E−H Bonds by a Boryl‐Substituted GeII Cation. Issue 1 (3rd December 2019) - Mangan, Robert J.; Rit, Arnab; Sindlinger, Christian P.; Tirfoin, Rémi; Campos, Jesús; Hicks, Jamie; Christensen, Kirsten E.; Niu, Haoyu; Aldridge, Simon
Abstract: The synthesis of a boryl‐substituted germanium(II) cation, [Ge{B(NDippCH)2 }(IPrMe)] +, (Dipp=2, 6‐diisopropylphenyl) featuring a supporting N‐heterocyclic carbene (NHC) donor, has been explored through chloride abstraction from the corresponding (boryl)(NHC)GeCl precursor. Crystallographic studies in the solid state and UV/Vis spectra in fluorobenzene solution show that this species dimerizes under such conditions to give [(IPrMe){(HCNDipp)2 B}Ge=Ge{B(NDippCH)2 }(IPrMe)] 2+ (IPrMe = 1, 3‐diisopropyl‐4, 5‐dimethylimidazolin‐2‐ylidene), which can be viewed as an imidazolium‐functionalized digermene. The dimer is cleaved in the presence of donor solvents such as [D8 ]thf or [D5 ]pyridine, to give monomeric adducts of the type [Ge{B(NDippCH)2 }(IPrMe)(L)] + . In the case of the thf adduct, the additional donor is shown to be sufficiently labile that it can act as a convenient in situ source of the monomeric complex [Ge{B(NDippCH)2 }(IPrMe)] + for oxidative bond‐activation chemistry. Thus, [Ge{B(NDippCH)2 }(IPrMe)(thf)] + reacts with silanes and dihydrogen, leading to the formation of Ge IV products, whereas the cleavage of the N−H bond in ammonia ultimately yields products containing C−H and B−N bonds. The facile reactivity observed in E−H bond activation is in line with the very small calculated HOMO–LUMO gap (132 kJ mol −1 ). Abstract : Cationic germanium : Chloride abstraction from the boryl/NHC stabilized Ge II precursor (IPrMe)GeCl{B(NDippCH)2 } yields [(IPrMe){(HCNDipp)2 B}Ge=Ge{B(NDippCH)2 }(IPrMe)] 2+ which can be viewed as an imidazolium‐functionalized digermene, and is cleaved in the presence of donor solvents yielding monomeric [Ge{B(NDippCH)2 }(IPrMe)(L)] + . The thf adduct is sufficiently labile that it can act as a convenient source of monomeric [Ge{B(NDippCH)2 }(IPrMe)] +, which undergoes oxidative bond‐activation chemistry.